2010
DOI: 10.1063/1.3517228
|View full text |Cite
|
Sign up to set email alerts
|

Novel spray pyrolysis for dye-sensitized solar cell

Abstract: In the area of photovoltaic, the silicon solar cell is the most popular and it has issues such as stability and scaling up cost. On the other hand, a dye-sensitized solar cell (DSSC) is one of the most promising candidates for a high-performance solar cell in the next generation, since it is fabricated by a simple manufacture process at relatively low cost. The focus of interest in this research paper is to mention the usage of maiden single and simple apparatus of spray pyrolysis thin film deposition to fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…roll to roll processes). Previous studies have demonstrated the possibility of titanium oxide synthesis by this technology [19][20][21][22]. For example, Castaneda et al and Conde-Gallardo et al have shown by X-ray diffraction that crystallization in anatase phase occurs over 300-400°C, [19,20] whereas Duminica et al have reported a fraction of rutile phase at high temperature [21].…”
Section: Introductionmentioning
confidence: 99%
“…roll to roll processes). Previous studies have demonstrated the possibility of titanium oxide synthesis by this technology [19][20][21][22]. For example, Castaneda et al and Conde-Gallardo et al have shown by X-ray diffraction that crystallization in anatase phase occurs over 300-400°C, [19,20] whereas Duminica et al have reported a fraction of rutile phase at high temperature [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for decades in the glass industry and in solar cell production [1], for powder production [48] and for electrodes and counter electrodes for dye-sensitized solar cells [49]. The method is used for deposition of thin ferrite films [50], thin films of the perovskite LaFeO 3 [51], thin films of TiO 2 (pure or modified) [52][53][54][55], films of poly-(methyl)methacrylate [28], and thin films of cerium-doped yttrium-iron garnet [56], each of them with potential applications in water purification, oxygen sensing, thermosensors, for deposition of thin yttria-stabilized zirconia films [1,57,58], for crystalline and non-crystalline iron oxide (α-Fe 2 O 3 ) thin films onto glass substrates at different temperatures [59,60], highly structured ZnO layers [61], transparent conducting zinc oxide thin films [62], lead(II) oxide thin films [63], nanoporous aluminum oxide [64], europium doped lanthanum oxide films [65], and UV excited green emitting Eu(II) activated BaAl 2 O 4 and SrAl 2 O 4 [66] and etc.…”
Section: Spray Pyrolysis Methods For Film Productionmentioning
confidence: 99%
“…TiO 2 films deposited on glass substrate have the properties required to convert solar energy into electrical energy or thermal energy. 4,5 The conditions for obtaining TiO 2 and its properties prepared by spray pyrolysis deposition (SPD) have been presented in Ref. 6.…”
Section: Introductionmentioning
confidence: 99%